Repurposing Cardiac Glycosides: Drugs for Heart Failure Surmounting Viruses - Škubník, Jan; Bejček, Jiří; Pavlíčková, Vladimíra Svobodová; Rimpelová, Silvie (Molecules (Basel, Switzerland), 2021)
Drug repositioning is a successful approach in medicinal research. It significantly simplifies the long-term process of clinical drug evaluation, since the drug being tested has already been approved for another condition. One example of drug repositioning involves cardiac glycosides (CGs), which have, for a long time, been used in heart medicine. Moreover, it has been known for decades that CGs also have great potential in cancer treatment and, thus, many clinical trials now evaluate their anticancer potential. Interestingly, heart failure and cancer are not the only conditions for which CGs could be effectively used. In recent years, the antiviral potential of CGs has been extensively studied, and with the ongoing SARS-CoV-2 pandemic, this interest in CGs has increased even more. Therefore, here, we present CGs as potent and promising antiviral compounds, which can interfere with almost any steps of the viral life cycle, except for the viral attachment to a host cell. In this review article, we summarize the reported data on this hot topic and discuss the mechanisms of antiviral action of CGs, with reference to the particular viral life cycle phase they interfere with.
Keywords: Virus Internalization; sodíko-draslíková ATPasa; srdeční selhání; Neoplasms; replikace viru; Digoxin; digitoxin; ouabain; virus entry; antivirové látky; digoxin; Ouabain; Drug Repositioning; pandemie; internalizace viru; SARS-CoV-2; přehodnocení terapeutických indikací léčivého přípravku; srdeční glykosidy; Na+/K+-ATPase; Antiviral Agents; lidé; Sodium-Potassium-Exchanging ATPase; Virus Replication; lanatoside C; Cardiac Glycosides; Heart Failure; Humans; drug repurposing; cardiac steroids; nádory; Pandemics; Digitoxin; coronavirus; COVID-19